Standing While Black: Distinguishing Lyons in Racial Profiling Cases - Garrett, Brandon L. (2000)
Plaintiffs challenging racial profiling must contend with the Supreme Court's decision in City of Los Angeles v. Lyons, which restricted standing for injunctive relief against government officials. This Note articulates a framework for assessing standing for injunctive relief based on case law following Lyons: Plaintiff must demonstrate a sufficiently credible threat of future harm where government conduct was authorized by a policy, practice, or custom and where plaintiff was law-abiding. Lyons analysis focuses exclusively on an individual's likelihood of future harm because the Court was reluctant to let the grievance of one individual support city-wide injunctive relief. Where racial profiling cases raise equal protection claims alleging that groups of individuals are targeted by police, the concerns supporting the Lyons requirement become less relevant. Although the Court has never explicitly distinguished Lyons, in the Court's equal protection decisions, standing is presumed where a group is harmed. Following these decisions, Lyons should be distinguished in racial profiling cases